(untitled) (Vietnam Journal of Community Medicine, 2022)
Objectives: Describe the current state of knowledge, attitude and practice on caring for febrile children of mothers whose children under 5 years of age are inpatient at Vinh Thuan district health Center in 2021. Research methoddology: A cross-sectional descriptive study using quantitative research methods, distributing questionnaires and interviewing mothers with children under 5 years of age inpatient treatment at Vinh Thuan District Health Center in 2021 with a set of questionnaires suitable presets. Results: Research on knowledge, the percentage of mothers who give the wrong concept of fever accounts for nearly 3 times as many mothers with the right concept. Hot baby sign is the most obvious sign of mothers, accounting for a high rate from 86%. Most mothers know that convulsions are a complication of fever, accounting for a high rate 86%. In terms of practice attitude, all mothers know that fever is a dangerous problem and need to be taken care of in children, accounting for 100%. When detecting fever in children, mothers know to feed their children many meals (46.7%) and drink more juice (20%). Conclusion: Regarding knowledge, 73.3% of mothers understood the concept of fever incorrectly. More than 90% of mothers recognize a child’s fever based on the signs of the baby being cranky and fussy. About the attitude of practice, about 46.7% of mothers gave their children many meals when they had a fever and 20% gave them fruit juice to drink.